The Development of Children's Early Numeracy Skills in The Piaget’s Preoperational Stage - Nugraha, Adi Cahya; Nuriadin, Ishaq (MATHEMA: JURNAL PENDIDIKAN MATEMATIKA, 2025)
Early numeracy skills are crucial for young children's cognitive and mathematical development, particularly during the preoperational stage (ages 2-7), when they begin to develop symbolic thinking and foundational mathematical concepts. This study investigates the progression of early numeracy skills in two preschool-aged children (Child H and Child K), focusing on their ability to engage with numeracy concepts such as counting, cardinality, numeral identification, and number combination. Using a qualitative case study approach, the research observes the children's numeracy behaviors through assessments and direct observation during play-based learning activities. Findings reveal notable differences in the children’s numeracy development: Child H demonstrates stronger skills in one-to-one counting, subitizing, number ordering, and problem-solving, while Child K shows emerging abilities but struggles with tasks such as number comparison and number combination. These differences highlight the variability in the development of numeracy skills, with confident children progressing more rapidly in their understanding of numbers and relationships. The study emphasizes the importance of concrete, hands-on learning experiences in developing mathematical thinking, mainly through physical manipulatives and interactive, game-based activities. The results underscore the need for tailored learning experiences to support children in the preoperational stage, which has implications for early childhood educators in fostering a strong mathematical foundation.